A rainbow in the desert : an anthology of early twentieth century Japanese children's literature - Ohta, Yukie, 1969-. (Armonk, N.Y. : M.E. Sharpe, 2001)
A collection of Japanese children's literature in translation spans three decades with contributions by major authors as well as familiar lullabies.
"An East gate book.".
Keywords: Children's literature, Japanese; Japanese literature -- Collections; Japan -- Literary collections; Japan -- Literary collections